Sensor data collecting system for biathlon - Brager, A. (Norges teknisk-naturvitenskapelige universitet, Fakultet for informasjonsteknologi og elektroteknikk (IE), Institutt for teknisk kybernetikk, 2019)
The purpose of this project was to develop further a Sensor Data Collecting System for Biathlon, an Olympic sport that combines cross-country skiing and target shooting. This is a wireless system that collects data from multiple relevant sensors which athletes and coaches can use to analyse and improve their performance.